Analisis Yuridis Terhadap Putusan Nomor: 1132/Pid.Sus/2016/Pn.Pbr Pekanbaru Pada Pelaku Tindak Pidana Penyelundupan Kosmetik Ilegal - Ita Maya Sari; Mexsasai Indra; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The crime of smuggling illegal cosmetics continues to increase, behavior that circulates illegal cosmetics goods that have been entrenched and institutionalized. The most vulnerable factors to illegal cosmetics smuggling are the supervisors who are less comparative in supervising each spot that is highlighted by smugglers and the lack of supervision by the BPOM in examining every cosmetics that are taught. The target of the perpetrators is to circulate aimed at the shop in order to get profit. Consumers must be wiser in choosing cosmetic products by paying attention to the Registration number of BPOM. The smuggling of illegal cosmetics has caused concern to the public, the perpetrators of the police spotlight only claim to get the illegal cosmetics from other people and they are entrusted. The case that came to the court was certainly a serious problem, a case that occurred in 2016 in the Pekanbaru District Court on behalf of Adi Putra Alias Awi. The judge sentenced him with light sentences with a large amount of evidence and the absence of fines. With regard to light sentences, it will certainly be difficult to make the illegal cosmetics smugglers deterrent, given the lack of supervision of illegal cosmetics smuggling that is increasingly widespread will cause harm to the Indonesian state. The purpose of writing this thesis, namely: first to find out the judge's consideration in the illegal cosmetics smuggling case in the legal cosmetic circulation of the judge's decision number 1132 / Pid.Sus / 2016 / PN.Pbr in Pekanbaru District Court, secondly, to find out the ideal idea related to the sentence given judge to the defendant related to the absence of fines in the decision. This type of research is normative juridical research or can also be called doctrinal law research. Data collection techniques in this study with the study of literature. From the results of the research problem there are two main things that were concluded, first, the growth of judges in case number 1132 / Pid.Sus / 2016 / PN.Pbr in Pekanbaru District Court, second, related to the imposition of sanctions in cases of illegal cosmetics distribution in case number 1132 / Pid .Sus / 2016 / PN.Pbr in Pekanbaru District Court. Keywords: Judge's Decision - Fines - Criminal Actions of Illegal Cosmetic Smuggling